Sirtuin 1 alleviates alcoholic liver disease by inhibiting HMGB1 acetylation and translocation - Juan Fu; Wei Deng; Jun Ge; Shengqi Fu; Panpan Li; Huazhi Wu; Jiao Wang; Yi Gao; Hui Gao; Tao Wu (PeerJ, 2023)
Background Alcoholic liver disease (ALD) encompasses a spectrum of liver disorders resulting from prolonged alcohol consumption and is influenced by factors such as oxidative stress, inflammation, and apoptosis. High Mobility Group Box 1 (HMGB1) plays a pivotal role in ALD due to its involvement in inflammation and immune responses. Another key factor, Sirtuin 1 (SIRT1), an NAD+-dependent deacetylase, is known for its roles in cellular stress responses and metabolic regulation. Despite individual studies on HMGB1 and SIRT1 in ALD, their specific molecular interactions and combined effects on disease advancement remain incompletely understood. Methods Alcohol-induced liver injury (ALI) models were established using HepG2 cells and male C57BL/6 mice. HMGB1 and SIRT1 expressions were assessed at the mRNA and protein levels usingreverse transcription-quantitative polymerase chain reaction, western blot, and immunofluorescence staining. The physical interaction between HMGB1 and SIRT1 was investigated using co-immunoprecipitation and immunofluorescence co-expression analyses. Cellular viability was evaluated using the CCK-8 assay. Results In patients with clinical ALI, HMGB1 mRNA levels were elevated, while SIRT1 expression was reduced, indicating a negative correlation between the two. ALI models were successfully established in cells and mice, as evidenced by increased markers of cellular and liver damage. HMGB1 acetylation and translocation were observed in both ALI cells and mouse models. Treatment with the SIRT1 agonist, SRT1720, reversed the upregulation of HMGB1 acetylation, nuclear translocation, and release in the ethyl alcohol (EtOH) group. Furthermore, SIRT1 significantly attenuated ALI. Importantly, in vivo binding was confirmed between SIRT1 and HMGB1. Conclusions SIRT1 alleviates HMGB1 acetylation and translocation, thereby ameliorating ALI.